Gender role on topic preference of senior secondary school students in mathematics (2007)
This study investigated the topic preference of senior secondary school students in mathematics and role gender plays on their preferences. Six hundred and forty senior secondary school II students selected through multi stage sampling were used.They provided data on thier preferred topics in mathematics by giving positions to the nine major mathematics topic in the senior secondary schools syllabus. they equally indicated their gender. The data collected was analyzed using descriptive statistics(frequency, cross tabulation). chi square test was also used to test the impact of gender on student's topic preference at the 0.05 level of significance. Number and numeration, algebraic process and statistics were found to be most preferred mathematics topic while bearing, probability and mensuration were most likely disliked mathematics topics among senior secondary students. Male and female students are found to be different in their preference for mathematics topics.It was also found that many males preferred number and numeration, algebraic process, mensuration and construction than thier female counterparts whereas many female students preferred plane geometry, trigonometry, bearing, statistics and probability than male students. Based on the findings og this study, it was recommended that mathematics teachers should organize various result oriented classroom activities, initiate strategies and innovations especially on the topic identified as disliked mathematics topics, that will boost interest of thier students. School counselors also should make use of these findings especially the gender impact on the students' preferences for mathematics topics to assist students overcome the dislike they have for some topics.